2007
DOI: 10.1111/j.1365-2125.2007.03009.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of allergen‐induced wheal and flare reactions by levocetirizine and desloratadine

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT• The reproducible and standardized histamine-induced wheal and flare model helps identify the objective effectiveness of antihistamines in humans, as well as their differences in onset and duration of action.• Some of the newest antihistamines have already been compared in a head-to-head setting using this model. However, their objective action at inhibiting the allergen-induced wheal and flare response has not been reported yet. WHAT THIS STUDY ADDS• The time-response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 23 publications
1
18
0
5
Order By: Relevance
“…Furthermore, the results strongly suggest that levocetirizine is the more effective of the 2 drugs in relieving whealing and itching, a conclusion supported by a previous 4-week trial in chronic urticaria 17 and wheal and flare studies comparing levocetirizine and desloratadine. [18][19][20][21] A recent study suggested that using higher doses of desloratadine in subjects with cold-induced urticaria had a beneficial effect. 22 This is in line with our results, which were, however, obtained in patients with difficult-to-treat urticaria.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, the results strongly suggest that levocetirizine is the more effective of the 2 drugs in relieving whealing and itching, a conclusion supported by a previous 4-week trial in chronic urticaria 17 and wheal and flare studies comparing levocetirizine and desloratadine. [18][19][20][21] A recent study suggested that using higher doses of desloratadine in subjects with cold-induced urticaria had a beneficial effect. 22 This is in line with our results, which were, however, obtained in patients with difficult-to-treat urticaria.…”
Section: Discussionmentioning
confidence: 98%
“…Максимальное уменьшение воспалительных проявлений наблюдалось через 24 ч после приема дезлоратадина (6%) и плацебо (33%) и через 7 ч после приема левоцети-ризина (87%) (рис. 6) [26][27][28][29].…”
Section: симптомыunclassified
“…Simons изуча-лись концентрации в крови и коже (при биопсии) и пода-вление образования кожных реакций в гистамин-инду- Примечание. Адаптировано по ссылкам [45][46][47][48][49][50][51][52][53][54][55][56].…”
Section: -е поколение (метаболиты препаратов 2-го поколения)unclassified